دراسة تأثير العوامل العشوائية على تخطيط أعمال البناء - جنود, علي; علي, حمزة; إبراهيم, سامر (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر عملية تحديد مدة المشروع بشكل دقيق من الأعمال الصعبة في المشاريع الهندسية نظرا" لارتباط مدة التنفيذ بعدد من العوامل التي يصعب التنبؤ بها بشكل مسبق. لذا كان الهدف من هذا البحث دراسة تأثير بعض من هذه العوامل من خلال صياغة استراتيجية منظمة نتمكن من خلالها التنبؤ بالزيادة المحتملة لمدة تنفيذ المشروع عن المدة المقدرة في الظروف الطبيعية. العوامل العشوائية المدروسة في هذا البحث شملت تأثير ثلاثة عوامل هي: تعطل الآليات, وغياب بعض أصحاب المهن وأخيرا" تأثير الظروف الجوية, ولإنجاز هذه الدراسة تم جمع البيانات المتعلقة بتلك العوامل من عدد من الشركات الإنشائية التي تعمل في قطاع البناء والتشييد, في مختلف المحافظات في سورية, وذلك خلال الفترة الممتدة من عام 1999- 2003. تم في هذه الدراسة استنتاج التوزيعات الاحتمالية الخاصة بكل عامل من العوامل المدروسة, كالتوزيع الاحتمالي لتعطل آليات المشروع المختلفة, وكذلك التوزيع الاحتمالي لدرجات الحرارة المنخفضة التي تؤدي لتوقف العمل, وأخيرا" التوزيع الاحتمالي لتغيب بعض أصحاب المهن المهمة خلال المشروع. يستخدم النظام المقترح تقنية المنطق الضبابي في صياغة القواعد المعرفية التي توضح تأثير اجتماع العوامل المختلفة السابقة على زيادة المدة المقررة لتنفيذ المشروع. تم إنشاء نظام حاسوبي يستخدم تقنية مونت كارلو في المحاكاة جنبا" إلى جنب مع المنطق الضبابي للوصول إلى القيمة المقترحة للقيمة, كما يتيح النظام المطور دراسة حساسية النتائج التي يقدمها تجاه التغيرات الحاصلة في عوامل المشروع, وكذلك في مقدمات ونتائج القواعد المعرفية المقترحة, مما يوفر أرضية بحثية هامة في هذا المجال. يعتبر هذا النظام أحد النظم المساعدة في اتخاذ القرار التي يمكن أن تستخدمها أجهزة تخطيط المشاريع الهندسية. Deciding the period of project exactly in considered one of difficult jobs in the engineering projects because of linking the period of execution with many factors which difficil the predict. So the aim of this search is to studying the influence of some these factors through an organization strategy modeling them enables us to predict the probable increase for the duration of the execution of the project upon the disposed period in natural circumstances. The random factors which are studied in this search include three factors: the cessation of machines, the absence of some proffesional, eventually the infulance of weather condition. To perform this study we have computing all data that are connected with that factors from many stractural companies which work in the field of building and constraction in different parts in Syria along the period between 1999-2003. In this study has done the inference of special probable distributions for every factor of elaborate factors as the probable distribution to the cessation of the different project machines. It also showed the probable dirstribution for the low temperature which causes stopping of the work. It eventually showed the probable dirstribution to absence some of professionals through the project. The proposal system uses the technique of fuzzy logic in modelling the encyclopedist rules which illustrate the influence of the assemblers for the previous different factors on increasing the decided period to execute the project. A computer system has done it which uses montcarlo technique in simulation side to side with the fuzzylogic to reach the proposed value for increasing The developed system allows to study the allergy of results which offer some mutations that happened in the project factors also in the performance and the results of proposal encyclopedist rules which available an important basic search in this field. This system is considered one of the systems in making decision which may be used by planning sets of the engineering projects.